2017
DOI: 10.1002/mbo3.519
|View full text |Cite
|
Sign up to set email alerts
|

Complete characterization of new isolates of Neptunomonas phycophila leads to emend its description and opens possibilities of biotechnological applications

Abstract: Five strains were isolated from gonad of Great scallop (Pecten maximus) broodstock in a Norwegian hatchery. The study of 16S rRNA gene sequences showed that these isolates belong to Neptunomonas phycophila, a bacterium originally isolated from a symbiont of the anemone Aiptasia tagetes from Puerto Rico. The gyrB and rpoB genes sequences confirmed the affiliation of the scallop isolates to this species. Phenotypic characterization was performed and some differences between the Norwegian isolates and the type st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 35 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…[59], Alteromonas sp. [60], Neptunomonas phycophila [61] and the Alphaproteobacteria Sulfitobacter sp. [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[59], Alteromonas sp. [60], Neptunomonas phycophila [61] and the Alphaproteobacteria Sulfitobacter sp. [13].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to this previous study, in the present work, the microcosm flasks were kept closed. The lower oxygen input to the experiment may explain the lower THPs removal since oxygen promotes the action of oxygenases, strong aliphatic hydrocarbons hydrocarbon-degrading enzymes [17,63], and isolation of the facultative anaerobe Neptunomonas phycophila [61] species. Nonetheless, the introduction of the lyophilized consortium accelerated the degradation of petroleum, a feature observed in some other studies.…”
Section: Discussionmentioning
confidence: 99%
“…4c-d), which could be because of different temperature optima among taxa. For example, prokaryote genera that were more abundant at 24°C, included Methylotenera (Kalyuzhnaya et al 2006), Neptunomonas (Diéguez et al 2017) and Methylophaga (Villeneuve et al 2013), genera that comprised some species with optimum growth temperatures ranging from 23 to 30°C (Lyubetsky et al 2020). In contrast, prokaryotic genera that were abundant at the 18°C treatment included Arcobacter (Van Driessche and Houf 2008), Colwellia (Techtmann et al 2016), and Saprospira (Saw et al 2012); these genera contain members that grow well at 18°C, and can tolerate temperatures as low as 4°C.…”
Section: Warming Seawater Drives Microbiome Shifts In M Gigas Spatmentioning
confidence: 99%
“…Together, this suggested that degradation of extracellular DNA is a specialised physiological feature of only some Nitrincolaceae members. Indeed, various members of Nitrincolaceae are known to be a relatively versatile in catabolic terms, whereby they are known to degrade various carbohydrates, alcohols, organic acids and complex polycyclic aromatic hydrocarbons 45 . Alternatively, the low abundance Nitrincolaceae detected in this study and that could not be sampled for genomically, may have distinct genomes that harbour more expansive gene complements for enabling DNA catabolism.…”
Section: Discussionmentioning
confidence: 99%